Dateringer - Elbek, Jørgen (Grundtvig-Studier, 1958)
Datings. By Jørgen Elbek. On the basis of a table of contents (compiled by N. F. S. Grundtvig) which is found among the manuscripts of the “Collection of Hymns for the Danish Church,” the author of the dissertation can with certainty date to the year 1836 14 of the hymns in the table mentioned. Eleven of these hymns have formerly been dated to 1837, one to 1837-39, and two to 1853! Besides, the study proves that from the very start Grundtvig carefully chose the sequence of the hymns in the “ Collection of Hymns.”